If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4x = 14 + 3x Solving 9 + 4x = 14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + 4x + -3x = 14 + 3x + -3x Combine like terms: 4x + -3x = 1x 9 + 1x = 14 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 1x = 14 + 0 9 + 1x = 14 Add '-9' to each side of the equation. 9 + -9 + 1x = 14 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 14 + -9 1x = 14 + -9 Combine like terms: 14 + -9 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| (2x+2)3=(x+8)4 | | 7(3+2x)=84 | | 25-3c=36 | | 60+2x=4x | | -19=18+x | | -45=3(1-4d) | | -2(x+4)=-2(x+8) | | 18=n-11 | | 0=-9t-27 | | -14=10+6q | | 5r+3=2r-8 | | 2x^5-6x^3+8x^2-5=0 | | 4+t=-11 | | (3+a)6=12a-12 | | -(8y+2)-(-7y-6)=-1 | | 8X=-20+6Y | | a-10=3 | | 2x^2-8x-42=68 | | -3*3.14+w=2*3.14 | | 8-(4x+2)=28 | | 5y=-8x-2 | | x^4+6x^3-2x^2-12x=0 | | 12.00-2.00h=10 | | -3*3.14+w=23.14 | | x/12=30/20 | | 6(x+5)+8=2x | | 4(4x-5)=2(8x-10) | | n/8*10/4=0 | | n/8*10/4= | | x^2-3x+54=0 | | 4t-13=2x+9 | | x-1=x+3 |